Grupos de friso - Inforsato, Ana Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Neste trabalho tratamos da classificação dos grupos de friso. Para realizar este objetivo abordamos elementos básicos da estrutura algébrica de grupo bem como apresentamos transformações geométricas, entre estas destacamos: translações, reflexões, rotações e reflexão com deslizamento. Além disso, localizamos este assunto como tópico da estrutura curricular do Ensino Fundamental e executamos uma atividade em sala de aula em que os alunos criaram frisos ornamentais.

In this work we deal with the classification of frieze groups. In order to accomplish this objective we approach basic elements of the algebraic group structure as well as present geometric transformations, among which we highlight: translations, reflections, rotations and glide reflection. In addition, we locate this subject as a topic of the curricular structure of Elementary School and perform a classroom activity in which the students created ornamental friezes.
Frieze groups
Keywords: Grupos de friso; Transformações geométricas; Isometrias; Simetrias; Frieze groups; Geometric transformations; Isometries; Symmetries